Effect of Massage, Foot Massage, and Warm Blanket Combination on Ankle Brachial Index in Diabetic Ulcer Risk - Rizki Mega Safitri; Tata Mahyuvi (Universitas STRADA Indonesia, 2025)
Background: Diabetic ulcers are chronic complications of diabetes mellitus that can lead to infection and gangrene if not properly treated. Complementary therapies can help prevent diabetic ulcers by improving blood circulation and maintaining vasodilation. Preventive measures include massage, foot massage, and the application of warm blankets to support smooth blood flow. Purpose: This study aimed to evaluate the effect of a combination of massage, foot massage, and warm blankets on changes in the Ankle Brachial Index (ABI) as a marker of diabetic ulcer risk. Method: The research employed a quasi-experimental design with a one-group pre-test and post-test approach. A total of 30 respondents were selected using total sampling, with inclusion criteria being female diabetes mellitus patients diagnosed for more than a year, aged over 30 years, and free from leg ulcers. Pre-test ABI measurements were conducted on the second day of week 1. The intervention involved a 30-minute combination of massage, foot massage, and warm blankets, administered twice a week over three weeks. Post-test ABI data were collected at the sixth meeting in the third week. Results: Before the intervention, the average ABI of respondents was 0.57, indicating a moderate risk. Following the intervention, the ABI improved to an average of 0.74, categorized as mild risk. Statistical analysis using the Wilcoxon test showed a significant effect (p < 0.05) of the intervention on ABI changes. Conclusion: In conclusion, the combination of massage, foot massage, and warm blankets is an effective complementary therapy for maintaining foot health in diabetes mellitus patients, thereby reducing the risk of diabetic ulcers.